P2tl Performance Program in the Installation of Postpaid and Prepaid Electricity Meters - Tjerie Pangemanan; Nelson L Maarial; Rudi I Bawenti; Alfa J Takahepis; Rivaldo E Gombo; Raski Pontut (Jurnal Syntax Admiration, 2025)
The Electricity Infrastructure Control and Maintenance (P2TL) program aims to increase efficiency and effectiveness in the installation of electricity meters, both postpaid and prepaid. This study analyzes the performance of the P2TL program by focusing on the comparison between the installation of postpaid and prepaid electricity meters, as well as their impact on operational efficiency and customer satisfaction. Objective: To assess the effectiveness of the P2TL program in the implementation of electricity meter installation, and to analyze the performance differences between postpaid and prepaid systems. The P2TL (Penertiban Pemakaian Tenaga Listrik) Performance Program plays a crucial role in ensuring the proper installation and regulation of postpaid and prepaid electricity meters. This program is designed to monitor, control, and prevent electricity usage violations, ensuring that energy distribution remains efficient, fair, and compliant with national electricity regulations. This study aims to evaluate the effectiveness of the P2TL program in enhancing the accuracy and security of electricity meter installations. By analyzing installation procedures, technical challenges, and consumer compliance, the research highlights key performance indicators that determine the success of P2TL in both postpaid and prepaid systems. Data collection was conducted through field observations, interviews with technical personnel, and analysis of customer feedback to understand the program’s impact on service quality and electricity loss prevention.